Kinetic‐Scale Turbulence in the Venusian Magnetosheath. Issue 2 (18th January 2021) - Bowen, T. A.; Bale, S. D.; Bandyopadhyay, R.; Bonnell, J. W.; Case, A.; Chasapis, A.; Chen, C. H. K.; Curry, S.; Dudok de Wit, T.; Goetz, K.; Goodrich, K.; Gruesbeck, J.; et al.
Abstract: While not specifically designed as a planetary mission, NASA's Parker Solar Probe (PSP) mission uses a series of Venus gravity assists (VGAs) in order to reduce its perihelion distance. These orbital maneuvers provide the opportunity for direct measurements of the Venus plasma environment at high cadence. We present first observations of kinetic scale turbulence in the Venus magnetosheath from the first two VGAs. In VGA1, PSP observed a quasi‐parallel shock, β  ∼ 1 magnetosheath plasma, and a kinetic range scaling of k −2.9 . VGA2 was characterized by a quasi‐perpendicular shock with β  ∼ 10, and a steep k −3.4 spectral scaling. Temperature anisotropy measurements from VGA2 suggest an active mirror mode instability. Significant coherent waves are present in both encounters at sub‐ion and electron scales. Using conditioning techniques to exclude these electromagnetic wave events suggests the presence of developed sub‐ion kinetic turbulence in both magnetosheath encounters. Key Points: Observations from Parker Solar Probe reveal kinetic scale turbulence in the Venus magnetosheath Differences in kinetic range spectral indices between flyby‐encounters are possibly due to shock geometry and kinetic plasma instabilities